Plastic design of orthotropic clamped circular plates - Kumar V. (My University, 2025)
The method of limit analysis is used to determine the load carrying capacities of thin orthotropic clamped circular plates composed of rigid perfectly plastic material and subjected to axially symmetric loading. The modified Tresca yield condition and its associated flow rules have been used in this study. Design charts for these loading conditions are constructed and an example is presented illustrating their use in the design of a pressure vessel head.